2011
DOI: 10.1016/s1836-9553(11)70003-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing pressure support does not enhance secretion clearance if applied during manual chest wall vibration in intubated patients: a randomised trial

Abstract: NCT01155648.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…This set of factors also favors microorganism multiplication and, thus, an increased incidence of ventilator-associated pneumonia (VAP). ( 6,7 )…”
Section: Introductionmentioning
confidence: 99%
“…This set of factors also favors microorganism multiplication and, thus, an increased incidence of ventilator-associated pneumonia (VAP). ( 6,7 )…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that these data do not support the indication or contraindication of bronchopulmonary hygiene by means of physical therapy in patients with COPD or bronchiectasis [7]. Another study reports that an increase in support pressure in intubated patients increases mucociliary clearance, whereas the addition of manual vibration with thoracic compression in combination with this increase in support pressure does not offer benefits regarding bronchopulmonary hygiene [26].…”
Section: Discussionmentioning
confidence: 99%
“…Esse estudo comparou a técnica de hiperinsuflação associada à vibrocompressão versus aspiração. No entanto, em outro estudo realizado por esse autor em 2011, não foi encontrada diferença nos mesmos parâmetros, quando comparado vibrocompressão isolada versus vibrocompressão associada à hiperinsuflação 21 . Esse fato pode significar que a variação dos valores hemodinâmicos e ventilatórios entre esses dois estudos foram causadas Os dados são expressos como média ± desvio padrão.…”
Section: Discussionunclassified